Epidemiological profile of patients treated at a psychosocial care center ad III - Paula Cândida da Silva Dias (Acta Scientiarum. Health Sciences, 2017)
This is a cross-sectional descriptive study aime d at identifying the epid emiological profile of the patients treated at a Psychosocial Care Center fo r Alcohol and other type III drugs.Data were collected in 2014 from the records of 519 users, using a previously prepared epidemiological form. Most of patients are men attheproductive age; with low schooling and low family income.Most make use of alcohol, have undergone previous treatments in psychiatric hospitals and attended the unit for treatment by influence of third parties, even when it is co ntemplated. The users of the service are people with serious social and health commitments and although they are increasing use of crack, which is the current concern of public policies, alcohol is still the drug of predilecti on and represents the gateway to other drugs